AN ANALYSIS OF THE INFLUENCE OF EDUCATION, PROFESSIONALISM, COMPETENCE, AND INDEPENDENCY ON THE QUALITY OF INTERNAL AUDIT RESULTS AND WORK EXPERIENCE AS A MODERATING VARIABLE AT PT BANK NEGARA INDONESIA (PERSERO) TBK REGION MEDAN. - Anna, Martha Siagian (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to find out, analyze, and prove empirically the influence of education, professionalism, competence, and independency on the quality of internal audit results and work experience as a moderating variable at PT Bank Negara Indonesia (Persero) Tbk Region Medan. The population was 48 internal auditor at PT Bank Negara Indonesia (Persero) Tbk Region Medan and 48 of them were used as the samples since they returned the questionnaires, taken by using census technique. The data were analyzed by using multiple linear regression analysis and residual test for moderating variable. The result of the research showed that, partially and simultaneously, there was the influence of education, professionalism, competence, and independency on the quality of internal audit results at PT Bank Negara Indonesia (Persero) Tbk Region Medan. Work experience as a moderating variable proved unable to intent the relationship of education, professionalism, competence, and independency on the quality of internal audit results at PT Bank Negara Indonesia (Persero) Tbk Region Medan.